Neurosífilis e infección por el virus de inmunodeficiencia humana. Una puesta al día - Silva R., Carlos; Abudinén A., Gabriel; Espinoza Y., Julio; Gutiérrez F., Sebastián (Revista Hospital Clínico Universidad de Chile, 2019)
Medical literature shows that the co-infection of syphilis and human immunodeficiency virus (HIV) is increasing dramatically worldwide. HIV infection and syphilis have a synergistic relationship. Syphilis increases the risk of HIV transmission and acquisition, while HIV affects the presentation, diagnosis, progression and response to syphilis treatment. The diagnosis of syphilis is made with a non-treponemal reactive test (VDRL or RPR) confirmed with a treponemal test (FTA-ABS or MHA-TP). The opportune diagnosis of neurosyphilis is essential, particularly in the asymptomatic stages, given the high risk of serious sequels and lethality. All patients co-infected with HIV and syphilis with neurological symptoms must be studied with PL and other complementary tests. There is controversy about when to perform a lumbar puncture in co-infected patients who do not have neurological symptoms. However, there is consensus that a CD4 count lower than 350/μl or RPR title greater than 1/32 has indication for the study of cerebrospinal fluid. Therapy with penicillin G in high doses is the treatment of choice, in addition to clinical and serological follow-up that must be done to these patients.